Osteoarthritis-dependent changes in antinociceptive action of Nav1.7 and Nav1.8 sodium channel blockers: An in vivo electrophysiological study in the rat. (4th June 2015) - Rahman, W.; Dickenson, A.H.
Highlights: MIA-dependent antinociceptive effect of ProTxII and A-803467 on neuronal activity. Changes in Nav 1.7 and 1.8 channel function contribute to osteoarthritic pain. Blocking Nav 1.7 and Nav 1.8 channels has therapeutic potential for the treatment of osteoarthritic pain. Abstract: Voltage-gated sodium channel blockers are not traditionally recommended for osteoarthritis (OA) pain therapy, but given the large peripheral drive that follows OA development there is a rationale for their use. Using a rat model of monosodium iodoacetate (MIA)-induced OA we used in vivo electrophysiology to assess the effects of the Nav 1.7- and Nav 1.8-selective antagonists, ProTxII and A-803467 respectively, on the evoked activity of spinal dorsal horn neurons in response to electrical, mechanical and thermal stimuli applied to the peripheral receptive field. These studies allow examination of the roles of these channels in suprathreshold stimuli, not amenable to behavioral threshold measures. Spinal administration of ProTxII significantly reduced neuronal responses evoked by mechanical punctate (von Frey (vF) 8–60 g) and noxious thermal (45 and 48 °C) stimuli in MIA rats only. A-803467 significantly inhibited neuronal responses evoked by vF 8–60 g and 48 °C heat after spinal administration; significantly inhibited responses evoked by brush, vFs 26–60 g and 40–48 °C stimuli after systemic administration; significantly inhibited the electrically evoked Aδ-, C-fiber, post-discharge, Input and wind-up responses and the brush, vFs 8–60 g and 45–48 °C evoked neuronal responses after intra plantar injection in the MIA group. In comparison A-803467 effects in the sham group were minimal and included a reduction of the neuronal response evoked by vF 60 g and 45 °C heat stimulation after spinal administration, no effect after systemic administration and an inhibition of the evoked response to 45 °C heat after intra plantar injection only. The observed selective inhibitory effect of ProTxII and A-803467 for the MIA-treated group suggests an increased role of Nav 1.7 and 1.8 within nociceptive pathways in the arthritic condition, located at peripheral and central sites. These findings demonstrate the importance of, and add to, the mechanistic understanding of these channels in osteoarthritic pain.